Painted metal plate
The use of a fluororesin and an acrylic resin block copolymer in the resin layer of painted metal plates enhances weather resistance and workability, while maintaining glossiness, thereby addressing the cracking and ductility issues in conventional fluororesin coatings.
Patent Information
- Application Number
- JP2021109175
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-30
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2041-06-30
AI Technical Summary
Fluororesin coatings on galvanized steel sheets tend to crack during molding due to the hardness of the magnesium-added galvanized layer, and long-term storage reduces the ductility of the fluororesin, leading to potential coating breaks. Additionally, conventional fluororesin coatings with acrylic resin may lose glossiness and weather resistance when exposed to ultraviolet rays.
A painted metal plate with a resin layer comprising a fluororesin and an acrylic resin block copolymer, where the acrylic resin is a block copolymer with a polymer block of an acrylic ester and a polymer block of a methacrylic ester, and the weight average molecular weight of the acrylic ester polymer block is 40,000 or less, is used to enhance weather resistance and maintain glossiness.
The solution provides a painted metal plate with excellent weather resistance and high workability even after long-term storage, while minimizing the reduction in glossiness, thus addressing the issues of cracking and reduced ductility in conventional fluororesin coatings.
Smart Images

Figure 0007649208000001 
Figure 0007649208000002 
Figure 0007649208000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a coated metal sheet. [Background technology]
[0002] Coated metal sheets are generally excellent in durability, weather resistance, and design, and are preferably used, for example, as exterior building materials. Among the coated metal sheets for exterior building materials, coated metal sheets having a fluororesin coating film are suitable for coated metal sheets that require long-term durability.
[0003] Known examples of coated metal sheets having a fluororesin coating include a fluororesin-coated stainless steel sheet having a transparent coating made of a mixed resin of polyvinylidene fluoride and acrylic resin on the surface of the stainless steel sheet, the transparent coating having a specific degree of crystallinity and hardness (see, for example, Patent Document 1). Also known is a fluororesin-coated steel sheet having a fluororesin-colored layer containing a fluororesin, an acrylic resin, an inorganic calcined pigment, and an organic pigment on the surface of the steel sheet, and a coating made of polyester with a specific glass transition temperature on the back of the steel sheet (see, for example, Patent Document 2).
[0004] It is known that crystallization of fluororesins progresses over time. That is, fluororesins have the property that the molecules are relatively mobile in a temperature range above the glass transition temperature (for example, about -40°C for polyvinylidene fluoride) and the property that they are crystalline. Therefore, fluororesins are likely to change from an irregular molecular arrangement structure (amorphous structure) to an ordered molecular arrangement structure (crystalline structure) in a temperature range above the glass transition temperature.
[0005] In addition, fluororesin has the property that the bonding strength between molecular chains becomes stronger when it crystallizes, so the ductility of a fluororesin-based coating film may decrease over time as the crystallization of the fluororesin progresses over time.
[0006] Therefore, painted metal sheets having a fluororesin coating are unlikely to break (crack) during forming immediately after production, when the ductility of the fluororesin coating is high. However, if the sheet is stored for a long period of time after production and then formed after the ductility of the fluororesin coating has decreased, the coating may break.
[0007] As a method for preventing deterioration of the workability of a fluororesin coating film over time, a coated metal sheet having a coating film of a fluororesin paint composition containing a fluorine-based copolymer resin, a fluororesin, and an acrylic resin has been proposed (see, for example, Patent Document 3). Also, a coated metal sheet having a resin layer containing a fluororesin and an acrylic resin has been proposed (see, for example, Patent Document 4). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2001-009367 A [Patent Document 2] JP 2008-087242 A [Patent Document 3] Japanese Patent Application Publication No. 9-87575 [Patent Document 4] JP 2019-142060 A Summary of the Invention [Problem to be solved by the invention]
[0009] In recent years, highly corrosion-resistant galvanized steel sheets having a magnesium-added galvanized layer have begun to be used as base sheets for painting. When a fluororesin coating film is formed on such highly corrosion-resistant galvanized steel sheets, the magnesium-added galvanized layer of the galvanized steel sheets is generally hard, and therefore the coating layer is prone to cracking during forming. If the coating layer is prone to cracking during forming, the fluororesin coating film is also prone to cracking during forming. Therefore, it is desired to make the fluororesin coating film less prone to cracking even after long-term storage and to improve processability.
[0010] In response to this, the processability can be improved by further incorporating an acrylic resin into the coating film, as in the above Patent Documents 3 and 4. However, coating films further incorporating an acrylic resin may experience a noticeable decrease in gloss when exposed to ultraviolet light for a long period of time, and may not be able to maintain sufficient weather resistance.
[0011] The present invention has been made in consideration of the above circumstances, and has an object to provide a coated metal sheet which has high processability even after long-term storage, in which the decrease in gloss is not noticeable, and which has good weather resistance. [Means for solving the problem]
[0012] The present invention relates to the following coated metal sheet.
[0013] The coated metal sheet of the present invention is a coated metal sheet having a metal sheet and a resin layer disposed thereon, the resin layer comprising a fluororesin (A) and an acrylic resin (B), the acrylic resin (B) being a block copolymer comprising a polymer block (b1) of an acrylic acid ester having an alkyl group having 3 or more carbon atoms and a polymer block (b2) of a methacrylic acid ester, and the weight average molecular weight of the polymer block (b1) is 40,000 or less. Effect of the Invention
[0014] According to the present invention, it is possible to provide a coated metal sheet which has high workability even after long-term storage, in which the decrease in gloss is not noticeable, and which has good weather resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] As described above, the reason why the decrease in gloss level is easily noticeable after weather resistance testing in conventional fluororesin coating films containing acrylic resin is not clear, but is presumed to be as follows.
[0016] When an acrylic resin has an alkyl group with 2 or less carbon atoms, it has good compatibility with fluororesins, but its processability is insufficient. When an acrylic resin with an alkyl group with 3 or more carbon atoms is used to improve processability, it is difficult to be compatible with fluororesins, so phase separation is likely to occur and large domains (dispersed phases) are likely to form. When a coating film in which such large domains are dispersed is irradiated with ultraviolet rays for a long period of time, the domains are decomposed and disappear due to the ultraviolet rays, and large recesses are likely to form on the surface. In other words, large unevenness is formed on the surface of the coating film, and the decrease in gloss is easily noticeable.
[0017] In contrast, the present invention uses a specific block copolymer as the acrylic resin, which makes it possible to make the decrease in gloss of the fluororesin coating film less noticeable even when it is irradiated with ultraviolet rays for a long period of time.
[0018] That is, the specific block copolymer contains a polymer block (b1) of an acrylic acid ester that has poor affinity with fluororesin and a polymer block (b2) of a methacrylic acid ester that has good affinity with fluororesin. Such a block copolymer can form small domains because it is moderately compatible with fluororesin. In addition, by adjusting the weight average molecular weight (Mw) of the acrylic acid ester polymer block (b1) to an appropriate range, the size of the domains can be further reduced. As a result, even if the domains are decomposed and disappeared by ultraviolet rays, the unevenness formed on the surface of the coating film can be made smaller than before, making the decrease in gloss less noticeable.
[0019] Furthermore, by using an acrylic ester having an alkyl group having 3 or more carbon atoms as the acrylic ester constituting the acrylic ester polymer block (b1), it is possible to make it function more easily as a soft segment, and the processability of the coated metal sheet can be further improved. The configuration of the present invention will be described below.
[0020] 1. Painted metal plate The coated metal sheet of the present invention has a metal sheet and a resin layer disposed thereon.
[0021] 1-1.Metal plate The metal plate can be selected from known metal plates, examples of which include cold-rolled steel plates, galvanized steel plates, Zn-Al alloy-plated steel plates, Zn-Al-Mg alloy-plated steel plates, aluminum-plated steel plates, stainless steel plates (including austenitic, martensitic, ferritic, and ferritic-martensite dual-phase plates), aluminum plates, aluminum alloy plates, and copper plates.
[0022] From the viewpoints of corrosion resistance and weight reduction, the metal sheet is preferably a plated steel sheet or a stainless steel sheet, and from the viewpoint of cost-effectiveness, a plated steel sheet is more preferable. From the viewpoint of further improving corrosion resistance, the metal sheet is preferably a hot-dip 55% Al-Zn alloy plated steel sheet, a hot-dip 55% Al-2% Mg-Zn alloy plated steel sheet, a Zn-Al-Mg alloy plated steel sheet, or an aluminum plated steel sheet. Among these, a zinc-based plated steel sheet is preferable, and a zinc-based plated steel sheet containing magnesium, such as a Zn-Al-Mg alloy plated steel sheet, is more preferable.
[0023] The thickness of the metal sheet can be appropriately set depending on the application of the coated metal sheet. For example, when the application of the coated metal sheet is an exterior building material, the thickness of the metal sheet is preferably, for example, 0.2 to 3.0 mm, and from the viewpoint of further improving the workability, the thickness is preferably 0.25 to 2.0 mm.
[0024] 1-2.Resin layer The resin layer is disposed in contact with the surface of the metal sheet or via another layer. From the viewpoint of making it easier to improve the weather resistance of the coated metal sheet, the resin layer is preferably disposed on the outermost surface of the coated metal sheet.
[0025] The resin layer contains a fluororesin (A) and an acrylic resin (B).
[0026] (Fluororesin (A)) The fluororesin (A) is not particularly limited, but is preferably a polymer containing a structural unit derived from vinylidene fluoride, and more preferably a fluorocopolymer containing a structural unit derived from vinylidene fluoride and a structural unit derived from hexafluoropropylene. Such a fluorocopolymer can impart durability, chemical resistance, heat resistance, abrasion resistance, weather resistance, corrosion resistance, and stain resistance to the resin layer while reducing crystallization over time.
[0027] The content of the structural unit derived from hexafluoropropylene in the fluorine-containing copolymer is not particularly limited, but from the viewpoint of reducing crystallization over time without impairing weather resistance, it is preferably 1 to 15 mass% based on the total of the structural units derived from vinylidene fluoride and the structural units derived from hexafluoropropylene. When the content of the structural units derived from hexafluoropropylene is 1 mass% or more, crystallization over time is easily reduced, and when it is 15 mass% or less, weather resistance is unlikely to be impaired. The total amount of the structural units derived from vinylidene fluoride and the structural units derived from hexafluoropropylene is preferably 100 mass% based on all structural units constituting the fluorine-containing copolymer.
[0028] The content of the structural unit derived from hexafluoropropylene and the structural unit derived from vinylidene fluoride in the fluorine-containing copolymer is 19 It can be measured by F-NMR.
[0029] The fluorine-containing copolymer may further contain structural units derived from other fluorine-containing monomers other than those mentioned above, if necessary. Examples of the other fluorine-containing monomers include tetrafluoroethylene, chlorotrifluoroethylene, trifluoroethylene, and vinyl fluoride.
[0030] The weight average molecular weight (Mw) of the fluororesin (A) is preferably 100,000 to 700,000, and more preferably 200,000 to 600,000. For example, from the viewpoint of easily increasing the weather resistance of the resin layer, it is preferable that the weight average molecular weight (Mw) of the fluororesin (A) is high. The weight average molecular weight (Mw) of the fluororesin (A) can be measured in terms of polystyrene by gel permeation chromatography (GPC).
[0031] The content of the fluororesin (A) is not particularly limited, but is preferably 50 to 85% by mass based on the entire base resin (of the resin layer) including the fluororesin (A) and the acrylic resin (B). When the content of the fluororesin (A) is 50% by mass or more, the properties of the fluororesin (A) such as weather resistance, corrosion resistance, and stain resistance are easily exhibited, and when the content is 85% by mass or less, the crystallization of the fluororesin (A) is easily suppressed by the acrylic resin (B), and not only the processability of the coated metal sheet is not easily impaired, but also the adhesion to the metal sheet is not easily impaired. From the above viewpoint, the content of the fluororesin (A) is more preferably 60 to 80% by mass based on the entire base resin including the fluororesin (A) and the acrylic resin (B).
[0032] (Acrylic resin (B)) The acrylic resin (B) is contained from the viewpoints of suppressing crystallization of the fluororesin (A) to improve the workability of the coated metal sheet and to increase the adhesion to the metal sheet.
[0033] The acrylic resin (B) is a block copolymer containing an acrylic acid ester polymer block (b1) and a methacrylic acid ester polymer block (b2).
[0034] Regarding the acrylic ester polymer block (b1): The acrylic acid ester polymer block (b1) (soft segment) contains a structural unit derived from an acrylic acid ester as a main component. From the viewpoint of improving the processability of the coated metal sheet, the acrylic acid ester is preferably an acrylic acid ester having an alkyl group having 3 or more carbon atoms (acrylic acid alkyl ester). The acrylic acid ester having an alkyl group having 3 or more carbon atoms may be an ester compound of acrylic acid and an alcohol having 3 or more carbon atoms.
[0035] The alkyl group contained in the acrylic acid ester may be linear or branched. Examples of the acrylic acid ester include propyl acrylate, n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, amyl acrylate, isoamyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, pentadecyl acrylate, dodecyl acrylate, 2-hydroxyethyl acrylate, and 2-methoxyethyl acrylate. Among them, from the viewpoint of easily improving the processability of the coated metal sheet, acrylic acid C4-8 alkyl ester is more preferable, and n-butyl acrylate is even more preferable. These acrylic acid esters may be acrylic acid esters having a homopolymer Tg of, for example, -70 to -30°C, preferably -50 to -40°C. The homopolymer Tg may be a value described in, for example, Takehisa Hattori, Hiroshi Sakamoto: Color Materials, 64, 471 (1991), etc.
[0036] The content of structural units derived from an acrylate ester having an alkyl group having 3 or more carbon atoms in the polymer block (b1) is not particularly limited, but is preferably 60% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, relative to all structural units constituting the polymer block (b1), and may be 100% by mass.
[0037] The polymer block (b1) may further contain a structural unit derived from a monomer other than the acrylic acid ester, if necessary. Examples of the monomer other than the acrylic acid ester include methacrylic acid ester, unsaturated carboxylic acid (e.g., acrylic acid, methacrylic acid, crotonic acid), aromatic vinyl compound (e.g., styrene, methylstyrene, etc.), olefin, conjugated diene, unsaturated nitrile (e.g., acrylonitrile, methacrylonitrile), acrylamide, methacrylamide, vinyl acetate, vinyl chloride, vinylidene chloride, vinylidene fluoride, etc. These may be used alone or in combination of two or more kinds.
[0038] The weight average molecular weight (Mw) of the polymer block (b1) may be 40,000 or less from the viewpoint of easily maintaining weather resistance. When the Mw of the polymer block (b1) is 40,000 or less, the domain (dispersed phase) of the polymer block (b1) can be made small. Therefore, even if the domain is decomposed and disappeared by ultraviolet rays, the unevenness formed on the surface of the resin layer can be made smaller than before, so that the decrease in gloss, i.e., the decrease in weather resistance, can be suppressed. From the same viewpoint, the Mw of the polymer block (b1) is preferably 20,000 to 40,000, more preferably 30,000 to 40,000.
[0039] The Mw of the polymer block (b1) can be calculated from the Mw of the acrylic resin measured by GPC and the monomer composition ratio determined by NMR measurement. in particular, 1) The Mw of the acrylic resin is measured by GPC. Specifically, the Mw of the acrylic resin can be measured based on the molecular weight of standard polystyrene from a chromatogram measured by gel permeation chromatography in accordance with JIS K 0124-2011. The measurement device and conditions can be the same as those in the examples described below. 2) Next, 1 The ratio of methacrylic acid esters (e.g., MMA) and acrylic acid esters (e.g., BA) present in an acrylic resin is quantified by H-NMR using the integral ratio of the peaks derived from the methyl group and methylene group adjacent to the ester bond, and the monomer mass ratio is calculated. 3) The Mw of the polymer block is calculated by multiplying the Mw of the acrylic resin measured in 1) above by the monomer mass ratio calculated in 2) above.
[0040] The Mw of the polymer block (b1) can be adjusted, for example, by the type and polymerization degree of the acrylic acid ester. For example, the Mw of the polymer block (b1) can be made smaller by using an acrylic acid ester having a branched alkyl group than by using an acrylic acid ester having a linear alkyl group.
[0041] The content of the polymer block (b1) in the block copolymer varies depending on the type of acrylic ester, but is preferably, for example, 30 to 85% by mass based on the total of the polymer block (b1) and the polymer block (b2). When the content of the polymer block (b1) is 30% by mass or more, the workability of the coated metal sheet is easily improved, and when it is 85% by mass or less, the weather resistance is not easily impaired. From the same viewpoint, the content of the polymer block (b1) is more preferably 50 to 85% by mass based on the total of the polymer block (b1) and the polymer block (b2).
[0042] The total content of the polymer block (b1) and the polymer block (b2) in the block copolymer is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more, and may be 100% by mass.
[0043] Regarding the methacrylic acid ester polymer block (b2): The methacrylic acid ester polymer block (b2) (hard segment) contains a structural unit derived from a methacrylic acid ester as a main component.
[0044] Examples of methacrylic acid esters include methacrylic acid alkyl esters such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, pentadecyl methacrylate, etc. Among them, from the viewpoint of easily obtaining compatibility with the fluororesin (A), methacrylic acid C1-2 alkyl esters are preferred, and methyl methacrylate is more preferred.
[0045] The content of structural units derived from a methacrylic acid ester (preferably methyl methacrylate) in the polymer block (b2) is not particularly limited, but is preferably 60% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, relative to all structural units constituting the polymer block (b2), and may be 100% by mass.
[0046] Polymer block (b2) may further contain structural units derived from other monomers than methacrylic acid esters, if necessary. Examples of other monomers include acrylic acid esters and the same as the other monomers in polymer block (b1).
[0047] The weight average molecular weight (Mw) of the polymer block (b2) is not particularly limited, but from the viewpoint of easily obtaining compatibility with the fluororesin (A), it is preferably 2000 to 20000. When the Mw of the polymer block (b2) is 2000 or more, compatibility with the fluororesin (A) is easily obtained, and when it is 20000 or less, processability is not easily impaired. From the same viewpoint, the Mw of the polymer block (b2) is preferably 3000 to 18000.
[0048] Regarding block connectivity: The bonding state of the polymer block (b1) and the polymer block (b2) is not particularly limited, and may be any of a diblock copolymer represented by (b1)-(b2), a triblock copolymer represented by (b1)-(b2)-(b1), (b2)-(b1)-(b2), and a multiblock copolymer represented by (b1)-((b2)-(b1))n, (b1)-((b2)-(b1))n-(b2), and (b2)-((b1)-(b2))n. Among them, from the viewpoint of easily adjusting the compatibility with the fluororesin (A) and easily controlling the phase separation structure, a block copolymer having a polymer block (b2) at both ends is preferred, and a triblock copolymer having a polymer block (b2) at both ends, i.e., a triblock copolymer of (b2)-(b1)-(b2) is more preferred.
[0049] When there are a plurality of polymer blocks (b1) or (b2), the monomer compositions and Mw of the plurality of polymer blocks (b1) or (b2) may be the same as or different from each other.
[0050] Physical properties of block copolymers: The glass transition temperature (Tg) of the acrylic resin (B) is not particularly limited, but from the viewpoint of improving the workability of the coated metal sheet, it is preferable that it is low, and it can be, for example, −50 to −10° C., preferably −40 to −20° C. The Tg of the acrylic resin (B) can be measured by differential thermal analysis (DTA).
[0051] The Tg of the acrylic resin (B) can be adjusted by the block composition and the monomer composition constituting the block. In order to lower the Tg of the acrylic resin (B), for example, it is preferable to increase the content of the polymer block (b1).
[0052] The weight average molecular weight (Mw) of the acrylic resin (B) is preferably from 30000 to 80000, and more preferably from 40000 to 75000. The weight average molecular weight of the acrylic resin (B) can be measured by the same method as described above.
[0053] The method for producing the block copolymer is not particularly limited and may be a known method. For example, a method of living polymerization of monomers for obtaining polymers constituting each block is common. Examples of the living polymerization method include a method of anionic polymerization in the presence of a mineral acid salt such as an alkali metal or alkaline earth metal salt using an organic alkali metal compound as a polymerization initiator, and a method of anionic polymerization in the presence of an organoaluminum compound using an organic alkali metal compound as a polymerization initiator. Among them, the method of anionic polymerization in the presence of an organoaluminum compound using an organic alkali metal compound as a polymerization initiator is preferred from the viewpoint that a block copolymer can be easily obtained with high purity and the molecular weight and composition ratio can be relatively easily adjusted.
[0054] The content of the acrylic resin (B) is preferably 2 to 30% by mass based on the entire base resin including the fluororesin (A) and the acrylic resin (B). When the content of the acrylic resin (B) is 2% by mass or more, the crystallization of the fluororesin (A) is suppressed, and not only the workability of the coated metal sheet is easily improved, but also the adhesion to the metal sheet is easily improved. When the content of the acrylic resin (B) is 30% by mass or less, the properties of the fluororesin (A), such as weather resistance, corrosion resistance, and stain resistance, are not easily impaired. From the above viewpoint, the content of the acrylic resin (B) is more preferably 2 to 20% by mass based on the entire base resin including the fluororesin (A) and the acrylic resin (B).
[0055] The total content of the base resin including the fluororesin (A) and the acrylic resin (B) can be, for example, 50% by mass or more relative to the resin layer. The base resin may be composed of the fluororesin (A) and the acrylic resin (B).
[0056] Regarding other ingredients: The resin layer may further contain other components in addition to those mentioned above, if necessary. Examples of the other components include other resins such as acrylic resin (C) other than those mentioned above, pigment particles, and the like.
[0057] (Acrylic resin (C)) The acrylic resin (C) is an acrylic resin different from the acrylic resin (B), and from the viewpoint of further enhancing weather resistance or suppressing a decrease in surface hardness, it is preferable that the acrylic resin (C) has a higher glass transition temperature (Tg) than the acrylic resin (B).
[0058] Specifically, the Tg of the acrylic resin (C) can be, for example, 0 to 110° C., preferably 50 to 110° C., and more preferably 70 to 110° C. The Tg of the acrylic resin (C) can be measured by the same method as described above.
[0059] Such an acrylic resin (C) is preferably a polymer mainly composed of structural units derived from methyl methacrylate. The content of the structural units derived from methyl methacrylate in the polymer is preferably 50% by mass or more, more preferably 70% by mass or more, and particularly preferably 100% by mass, based on all structural units constituting the polymer.
[0060] The polymer may further contain structural units derived from other monomers. Examples of other monomers include methacrylic acid esters and acrylic acid esters other than methyl methacrylate, as well as the same as the other monomers described above. Among them, methacrylic acid C2-6 alkyl esters and acrylic acid C1-6 alkyl esters are preferred. Such a polymer may be a random copolymer.
[0061] The content of the acrylic resin (C) is preferably 10 to 30% by mass, more preferably 10 to 20% by mass, based on the total base resin including the fluororesin (A) and the acrylic resin (B). When the content of the acrylic resin (C) is equal to or more than the lower limit, the weather resistance of the resin layer is further increased and the surface hardness is easily maintained, and when the content is equal to or less than the upper limit, the processability of the coated metal sheet is not easily impaired. The acrylic resin (B) / acrylic resin (C) ratio can be, for example, 1 / 9 to 3 / 7 (mass ratio).
[0062] (pigment particles) The pigment particles may be dispersed in the resin layer.
[0063] The pigment particles may be color pigment particles, gloss control agent particles, or extender pigment particles. One type of pigment particles may be used, or two or more types of pigment particles may be used.
[0064] The color pigment particles may be either organic or inorganic color pigment particles that are generally available as color pigments for paints. The color pigment particles are non-transparent and can impart a color tone to the resin layer to form a colored coating film.
[0065] Examples of inorganic color pigments include titanium oxide, chromium oxide, carbon black, iron black, iron oxide yellow, titanium yellow, red iron oxide, Prussian blue, cobalt blue, cerulean blue, ultramarine blue, cobalt green, and molybdenum red.
[0066] Examples of organic color pigments include Quinacridone Red, Lithol Red B, Brilliant Scarlet G, Pigment Scarlet 3B, Brilliant Carmine 6B, Lake Red C, Lake Red D, Permanent Red 4R, Bordeaux 10B, Fast Yellow G, Fast Yellow 10G, Para Red, Watching Red, Benzidine Yellow, Benzidine Orange, Bonn Maroon L, Bonn Maroon M, Brilliant Fast Scarlet, Vermilion Red, Phthalocyanine Blue, Phthalocyanine Green, Fast Sky Blue, and Aniline Black.
[0067] The color pigment particles may be particles of a calcined pigment of a complex oxide containing a metal component. Examples of calcined pigments include CoAl, CoCrAl, CoCrZnMgAl, CoNiZnTi, CoCrZnTi, NiSbTi, CrSbTi, FeCrZnNi, MnSbTi, FeCr, FeCrNi, FeNi, FeCrNiMn, FeZn, CoCr, MnCo, and SnZnTi.
[0068] The color pigment particles may also be metallic pigment particles, examples of which include Al flakes, resin-coated Al flakes, metal oxide-coated Al flakes, Ni flakes, Cu flakes, and stainless steel flakes.
[0069] The color pigment particles may also be pearlescent pigment particles. Examples of pearlescent pigment particles include titanium oxide-coated mica, iron oxide-coated mica, and titanium oxide-iron oxide-coated mica.
[0070] The number-average particle size of the color pigment particles is not particularly limited, but is usually 3 μm or less, and preferably 0.01 to 1.5 μm. If the particle size of the color pigment particles is smaller, the content of the color pigment particles in the resin layer can be increased. From this viewpoint, the number-average particle size of the color pigment particles is preferably 2.0 μm or less, and more preferably 0.5 μm or less.
[0071] The content of the color pigment particles varies depending on the particle size of the color pigment particles, but from the viewpoint of coloring properties obtained by blending the color pigment particles in the resin layer, it is preferably, for example, 10 to 40% by mass relative to the resin layer.
[0072] The gloss control particles can be added for the purpose of imparting a desired gloss to the resin layer or for the purpose of forming unevenness on the upper surface of the resin layer. Examples of materials for the gloss control particles include inorganic materials including silica and calcium carbonate, and resin materials such as acrylic resin, urethane resin, benzoquanamine resin, styrene resin, polyethylene resin, polypropylene resin, and fluororesin.
[0073] The number-average particle size of the gloss control particles is preferably 3 μm or less. Since the average particle size of commercially available gloss control particles is usually more than 3 μm, when using commercially available gloss control particles, it is preferable to separate particles having a particle size of 3 μm or less by classification.
[0074] The content of the gloss control particles varies depending on the particle size of the gloss control particles, but from the viewpoint of expressing the desired design by incorporating the gloss control particles in the resin layer, it is preferable that the content be, for example, 0 to 10% by mass relative to the resin layer.
[0075] The extender pigment particles are pigments contained in the resin layer from the viewpoints of adjusting the hardness of the resin layer and reducing the cost of the paint (bulk-increasing effect), and generally do not affect the color tone of the resin layer. Since the extender pigment particles are usually cheaper than the fluororesin (A), it is preferable that the resin layer contains the extender pigment particles. In addition, it is preferable that the extender pigment particles have a high visible light transmittance. Examples of the extender pigment particles include barium sulfate, titanium oxide, silica, and calcium carbonate particles.
[0076] The number average particle size of the extender pigment particles is preferably, for example, 0.01 to 1 μm.
[0077] The content of the extender pigment particles is preferably 0 to 10% by mass based on the resin layer.
[0078] The content (total content) of the pigment particles is preferably 10 to 50 mass% relative to the resin layer. Even if the content of the pigment particles is within the above range, by including the fluororesin (A) and the acrylic resin (B), cracks in the resin layer originating from around the pigment particles can be suppressed, and the workability of the coated metal sheet can be improved.
[0079] (Physical Properties) The thickness of the resin layer is appropriately set depending on the application of the coated metal sheet, and is preferably, for example, 5 to 50 μm. If the thickness of the resin layer is 50 μm or less, it is not necessary to apply a large amount of paint when producing the resin layer, and it is possible to make it difficult for paint defects such as popping (bubbles or holes) to occur when the paint film is heated and solidified. The thickness of the resin layer is more preferably 10 to 35 μm.
[0080] The thickness of the resin layer can be represented by the average value of the distance from the bottom surface to the surface at multiple points (for example, 10 arbitrarily selected points) of the resin layer.
[0081] The thickness of the resin layer can be appropriately determined taking into consideration the content of pigment particles, color tone, degree of ultraviolet shielding, and degree of processing during forming of the coated metal sheet.
[0082] For example, when the content of pigment particles in the resin layer is high, when the color tone brightness (L value defined by JIS) of the pigment particles, which are color pigments, is low, and when the ultraviolet shielding rate of the pigment particles is high, the color development of the resin layer due to the pigment particles (color concealment ability against the color of the base) and the ultraviolet shielding rate of the base are high. Therefore, in these cases, the thickness of the resin layer can be made smaller. Also, when the degree of processing is low, the ductility required for the resin layer is low, so the thickness of the resin layer can be made smaller.
[0083] On the other hand, from the viewpoint of maintaining long-term adhesion between the resin layer and its base (suppressing interfacial rupture for a long period of time), it is preferable to reduce the UV transmittance of the resin layer, and to achieve this, it is preferable to increase the thickness of the resin layer.
[0084] Thus, the lower limit of the thickness of the resin layer cannot be generally stated, but for example, if the degree of processing is equivalent to 4T bending and the L value of the pigment particles (e.g., titanium oxide particles) that are the coloring pigment exceeds 80, the thickness of the resin layer is preferably 20 μm or more, and more preferably 25 μm or more. Also, if the degree of processing is the above and the L value of the pigment particles (e.g., iron-chromium calcined pigment particles) that are the coloring pigment is 70 or less, the thickness of the resin layer is preferably 15 μm or more, and more preferably 18 μm or more.
[0085] When other layers are arranged, the thickness of the resin layer can be determined taking into consideration the presence of the other layers. For example, when the coated metal sheet has an undercoat layer and a resin layer, the thickness of the resin layer can be, for example, 10 to 35 μm from the viewpoint of improving design, corrosion resistance, and processability over time.
[0086] (phase separation structure) The resin layer may have a phase-separated structure having a matrix (continuous phase) mainly composed of the fluororesin (A) and domains (dispersed phase) mainly composed of the acrylic resin (B). In particular, since the acrylic resin (B) is a block copolymer as described above, it is compatible with the fluororesin (A) and easily undergoes phase separation to an appropriate degree, and small domains (dispersed phase) are uniformly dispersed.
[0087] The average particle size of the domains mainly composed of the acrylic resin (B) can be, for example, 5 to 70 nm, preferably 10 to 60 nm. When the average particle size of the domains is equal to or larger than the lower limit, the processability of the coated metal sheet is easily improved, and when it is equal to or smaller than the upper limit, the decrease in gloss is less noticeable and good weather resistance is easily maintained.
[0088] The phase-separated structure can be confirmed by observation with a transmission electron microscope (TEM). 1) First, after embedding the resin layer, the surface is polished using an ultramicrotome and then stained with vapor of metal oxide to selectively stain only the dispersed phase out of the dispersed phase and matrix phase. Then, ultrathin sections are prepared using an ultramicrotome to obtain TEM observation samples. These are then observed at 100,000 magnifications using a transmission electron microscope (TEM). 2) From the obtained TEM image, the particle sizes of 50 randomly selected stained domains (dispersed phase) are measured, and the average of these is taken as the average particle size.
[0089] 1-3.Other layers The coated metal sheet may further have layers other than the resin layer as necessary. Examples of the other layers include a chemical conversion layer, an undercoat layer, and an intermediate coat layer. For example, the coated metal sheet preferably has a metal sheet, a chemical conversion layer, an undercoat layer, and the above-mentioned resin layer in this order; more preferably has a metal sheet, a chemical conversion layer, an undercoat layer, an intermediate coat layer, and the above-mentioned resin layer in this order. In other words, the resin layer preferably functions as a top coat layer.
[0090] 1-3-1. Chemical conversion layer The chemical conversion coating layer can be disposed directly on the metal sheet, i.e., between the metal sheet and the resin layer, for the purpose of improving the adhesion and corrosion resistance of the painted metal sheet. The chemical conversion coating layer is a layer formed in contact with the surface of the metal sheet, and is composed of a composition that is attached to the surface of the metal sheet by pre-painting treatment. Examples of the chemical conversion coating layer include non-chromate-based coatings and chromate-based coatings. Both of these are coatings formed by rust prevention treatment.
[0091] Non-chromate-based coatings are preferred from the viewpoint of improving corrosion resistance and reducing the environmental burden in the production and use of coated metal sheets, while chromate-based coatings are preferred from the viewpoint of improving corrosion resistance.
[0092] Examples of non-chromate-based coatings include Ti-Mo composite coatings, fluoroacid-based coatings, phosphate coatings, resin-based coatings, resin and silane coupling agent-based coatings, silica-based coatings, silica and silane coupling agent-based coatings, zirconium-based coatings, and zirconium and silane coupling agent-based coatings.
[0093] The amount of the non-chromate coating can be determined appropriately depending on the type of coating. For example, the amount of the Ti-Mo composite coating is 10 to 500 mg / m2 in terms of total Ti and Mo. 2 The amount of the fluoroacid-based coating is preferably 3 to 100 mg / m in terms of fluorine or total metal elements. 2 The amount of the phosphate coating is preferably 0.1 to 5 g / m in terms of elemental phosphorus. 2 The amount of the resin coating is preferably 1 to 500 mg / m2 in terms of resin. 2 The amount of the resin and silane coupling agent coating is preferably 0.1 to 50 mg / m2 in terms of silicon. 2 The amount of the silica-based coating is preferably 0.1 to 200 mg / m2 in terms of Si. 2 The amount of silica and silane coupling agent coating is preferably 0.1 to 200 mg / m2 in terms of Si. 2The coating weight of the zirconium-based film is preferably 0.1 to 100 mg / m2 in terms of Zr. 2 The amount of the zirconium and silane coupling agent coating is preferably 0.1 to 100 mg / m2 in terms of Zr. 2 It is preferable that:
[0094] Examples of chromate-based coatings include paint-on chromate coatings and phosphoric acid-chromic acid-based chromate anti-rust coatings. The coating weight of these chromate-based coatings is 20 to 80 mg / m2 in terms of chromium element. 2 It is preferable that:
[0095] 1-3-2. Undercoat layer The undercoat layer can be disposed between the metal sheet and the resin layer from the viewpoint of improving the adhesion and corrosion resistance of the resin layer in the coated metal sheet. The undercoat layer is formed on the surface of the metal sheet or on the surface of the chemical conversion coating layer.
[0096] The undercoat layer may contain a resin, examples of which include fluororesins, polyester resins, modified silicone resins, acrylic resins, epoxy resins, phenoxy resins, urethane resins, and vinyl chloride resins.
[0097] When these resins have a crosslinkable group such as a hydroxyl group, a carboxyl group, a glycidyl group, an active halogen atom, or an isocyanate group, they may be crosslinked with a curing agent. The curing agent may be appropriately selected depending on the type of crosslinkable group. For example, examples of curing agents for curing epoxy resins include amine compounds, acid anhydrides, and imidazole compounds. Examples of curing agents for curing resins having hydroxyl groups include melamine compounds and isocyanate compounds.
[0098] The undercoat layer may further contain additives such as anti-rust pigment particles, color pigment particles, metallic pigment particles, pearl pigment particles, extender pigment particles, gloss regulator particles, etc. Examples of the anti-rust pigment particles include non-chromium-based anti-rust pigment particles including modified silica, vanadate, magnesium hydrogen phosphate, magnesium phosphate, zinc phosphate, aluminum polyphosphate, etc., and chromium-based anti-rust pigment particles including strontium chromate, zinc chromate, barium chromate, calcium chromate, etc.
[0099] Examples of colored pigment particles include titanium oxide, chromium oxide, carbon black, iron black, iron oxide yellow, titanium yellow, red iron oxide, Prussian blue, cobalt blue, cerulean blue, ultramarine blue, cobalt green, molybdenum red, quinacridone red, lithol red B, brilliant scarlet G, pigment scarlet 3B, brilliant carmine 6B, lake red C, lake red D, permanent red 4R, bordeaux 10B, fast yellow G, fast yellow 10G, para red, watching red, benzig The pigments include particles such as fluorine yellow, benzidine orange, Bonn Maroon L, Bonn Maroon M, brilliant fast scarlet, vermilion red, phthalocyanine blue, phthalocyanine green, fast sky blue, aniline black, CoAl, CoCrAl, CoCrZnMgAl, CoNiZnTi, CoCrZnTi, NiSbTi, CrSbTi, FeCrZnNi, MnSbTi, FeCr, FeCrNi, FeNi, FeCrNiMn, FeZn, CoCr, MnCo, and SnZnTi.
[0100] Examples of metallic pigment particles include Al flakes, resin-coated Al flakes, metal oxide-coated Al flakes, Ni flakes, Cu flakes, and stainless steel flakes. Examples of pearl pigment particles include titanium oxide-coated mica, iron oxide-coated mica, and titanium oxide-iron oxide-coated mica. Examples of extender pigment particles include particles of barium sulfate, titanium oxide, silica, and calcium carbonate. Examples of gloss regulator particles include inorganic materials such as silica and calcium carbonate, and resin materials such as acrylic resins, urethane resins, benzoquanamine resins, styrene resins, polyethylene resins, polypropylene resins, and fluororesins.
[0101] The content of these additives is not particularly limited. For example, by incorporating a pearl pigment in the resin layer and providing an undercoat layer with low brightness between the resin layer and the metal plate, the color tone and brilliance unique to the pearl pigment can be imparted. In addition, by adding large-diameter pigment particles with a particle size of about several tens of μm to the undercoat layer, unevenness can be formed at the interface between the undercoat layer and the resin layer, and the adhesion of the resin layer can be further improved, and the formation of unevenness on the surface of the painted metal plate can further improve low gloss. In addition, the content of the extender pigment particles in the undercoat layer is preferably 0 to 30% by mass. In addition, the content of the rust-preventive pigment particles in the undercoat layer is preferably 10 to 40% by mass.
[0102] The thickness of the undercoat layer is not particularly limited, but is preferably, for example, 1 to 10 μm, and more preferably 3 to 7 μm.
[0103] 1-3-3. Intermediate layer The intermediate coat layer can be disposed between the undercoat layer and the resin layer from the viewpoint of improving the adhesion between the layers and the corrosion resistance of the coated metal sheet.
[0104] The intermediate layer may be composed of a resin composition containing a thermoplastic resin, as in the undercoat layer, or may be composed of a cured product of a resin composition containing a curable resin and a curing agent. The intermediate layer may further contain an additive, as in the undercoat layer. The additive may be, for example, the same as that described for the resin layer.
[0105] The thickness of the intermediate coating layer is not particularly limited, but is preferably, for example, 3 to 20 μm, and more preferably 5 to 15 μm.
[0106] 2. Manufacturing method of painted metal sheet The coated metal plate can be produced by a known coating film production method. For example, the coated metal plate can be produced through the steps of 1) forming a coating film of a paint for a resin layer (resin coating) on a metal plate, 2) solidifying (baking) the coating film of the resin coating, and 3) quenching and crystallizing the solidified (baked) coating film.
[0107] Regarding step 1) The resin coating may be prepared by dispersing or dissolving the above-mentioned components in a solvent. Examples of the solvent include hydrocarbons such as toluene and xylene, esters such as ethyl acetate and butyl acetate, ethers such as cellosolve, and ketones such as methyl isobutyl ketone, methyl ethyl ketone, isophorone, and cyclohexanone.
[0108] The resin coating may further contain other components as necessary. Examples of the other components include a curing agent, a curing catalyst, and a hydrophilizing agent.
[0109] A curing agent is added to a resin coating material when the base resin, such as a fluororesin (A) or an acrylic resin (B), has a crosslinkable group, such as a hydroxyl group, a carboxyl group, a glycidyl group, an active halogen atom, or an isocyanate group, and crosslinks the base resin when the coating material is baked.
[0110] The curing agent can be appropriately selected from known curing agents depending on the type of base resin, baking conditions, etc. For example, when the base resin has a hydroxyl group, etc., the curing agent can be, for example, a melamine compound or an isocyanate compound. Examples of the melamine compound include imino group type, methylol imino group type, methylol group type, or fully alkyl group type melamine compounds. The isocyanate compound may be any of aromatic, aliphatic, and alicyclic, and examples include m-xylene diisocyanate, hexamethylene diisocyanate, naphthalene diisocyanate, isophorone diisocyanate, and block compounds thereof.
[0111] The curing catalyst is a component that accelerates the curing of the coating film or the crosslinking of the base resin, and can be appropriately selected from known components having such catalytic action.
[0112] The hydrophilizing agent is suitable as an additive for the resin layer, and can be contained in the resin coating material from the viewpoint of preventing rain streaks on the resin layer. Examples of the hydrophilizing agent include partial hydrolysis condensates of tetraalkoxysilane.
[0113] The coating can be carried out by a known method such as roll coating, curtain flow coating, spray coating, or dip coating.
[0114] Regarding step 2 (baking process) The resulting resin coating film is then solidified (baked).
[0115] Specifically, the solvent is evaporated from the resin paint and the resin paint is baked to solidify the coating film. If the resin paint contains a curing agent, the solvent is evaporated from the resin paint and the resin paint is baked to harden the coating film.
[0116] The resin coating can be solidified by baking the coating with heat. For example, the metal plate coated with the resin coating is heated to a temperature of 200 to 260°C.
[0117] Regarding step 3 (crystallization process) The solidified (baked) coating film is quenched and crystallized to obtain a resin layer.
[0118] That is, the coating film solidified by heating is cooled from a temperature (200°C) equal to or higher than the melting temperature of the fluororesin (A) to a temperature (70°C) at which the molecular motion of the fluororesin (A) slows down and crystal growth becomes difficult, at a cooling rate of 130°C / sec or more (crystallization step). From the viewpoint of preventing deterioration of processability due to the generation of coarse crystals, a faster cooling rate is preferable, and a cooling rate of 250°C / sec or more is preferable.
[0119] The coating film can be cooled by a known method such as air cooling, water cooling, standing to cool, contacting with a cooling member, or a combination of these.
[0120] The crystallization step may be carried out immediately after the coating film has solidified, or may be carried out after the coating film that has been solidified at a temperature lower than the melting temperature has been heated to a temperature equal to or higher than the melting temperature.
[0121] Other processes The method for producing a coated metal sheet may further include other steps in addition to those described above, as necessary. Examples of the other steps include a step of forming a chemical conversion coating, a step of forming an undercoat layer, and a step of forming an intermediate coat layer.
[0122] The step of forming the chemical conversion coating can be carried out by applying an aqueous chemical conversion solution to the surface of a metal sheet by a known method such as roll coating, spin coating, spraying, etc., and then drying the metal sheet without rinsing it with water. From the viewpoint of productivity, the drying temperature and drying time of the metal sheet are preferably, for example, 60 to 150°C at the temperature reached by the metal sheet, and 2 to 10 seconds.
[0123] The step of forming the undercoat layer can be carried out by applying a paint for the undercoat layer (undercoat paint) and curing the resulting film. The undercoat paint may contain a solvent and additives as necessary. The undercoat paint is prepared by uniformly mixing and dispersing the above-mentioned materials. The coating film of the paint is prepared by baking the metal plate by heating the metal plate at a temperature of 180 to 260°C, which is the temperature reached by the metal plate, for example.
[0124] The step of forming the intermediate coat layer can be carried out in the same manner as described above by applying a paint for the intermediate coat layer (intermediate coat paint) and then solidifying the resulting coating film. EXAMPLES
[0125] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.
[0126] 1. Preparation of the painted plate (Preparation of metal plate) A 55% aluminum, 2% magnesium, zinc alloy plated steel sheet (manufactured by Nippon Steel & Sumitomo Metal Corporation, SGL (registered trademark), thickness 0.35 mm, AZ150) was degreased with an alkali.
[0127] (Formation of chemical conversion layer) Next, a non-chromate rust-preventive treatment solution having the following composition was applied to the surface of the alkaline-degreased plated steel sheet, and the plated steel sheet after application was dried at 100°C without being rinsed with water. As a result, the plated steel sheet was degreased to a concentration of 10 mg / m2 in terms of Ti. 2 A non-chromate rust prevention treatment (formation of a chemical conversion coating layer) was performed with a coating amount of 1000g. Hexafluorotitanic acid 55g / L Hexafluorozirconate 10g / L Aminomethyl-substituted polyvinylphenol 72g / L Water Remaining
[0128] (Formation of undercoat layer) Next, an epoxy resin-based undercoat paint having the following composition was applied to the surface of the plated steel sheet after the above-mentioned non-chromate rust-proofing treatment, and then the plated steel sheet was heated so that the temperature reached by the plated steel sheet reached 200°C, to obtain a chromate-free plated steel sheet having an undercoat paint film with a dry film thickness of 5 μm. This was used as the painted base sheet. The clear paint was "NSC680" (a paint containing an amine-modified epoxy resin and an isocyanate-based curing agent) manufactured by Nippon Paint Industrial Coatings Co., Ltd. Phosphate mixture 15% by volume (23% by mass) (based on solids) Barium sulfate 5% by volume (15% by mass) (based on solid content) Silica 1% by volume (1% by mass) (based on solid content) Clear paint remaining
[0129] 2. Preparation of Fluoropolymer Paint 2-1. Preparation of materials (Fluorine resin) Fluororesin 1: Copolymer of vinylidene fluoride (VDF) and hexafluoropropylene (HFP) (VDF / HFP = 94 / 6 mass ratio) (Arkema "Kynar Flex LBG", weight average molecular weight 450,000) Fluorine resin 2: Polyvinylidene fluoride (Arkema "Kynar 500")
[0130] (Acrylic resin) <Preparation of acrylic resin 1> In a toluene solution, hexamethyltriethylenetetramine, isobutylbis(2,6-di-t-butyl-4-methylphenoxy)aluminum were used as a catalyst to polymerize the polymer block (b2-1) of methyl methacrylate, and then 75 parts by mass of n-butyl acrylate were added dropwise to polymerize the polymer block (b1) of n-butyl acrylate, and 12.5 parts by mass of methyl methacrylate were added dropwise to polymerize the polymer block (b2-2) of methyl methacrylate. Finally, the polymerization was terminated with methanol to obtain a block copolymer (B-1) which is a triblock copolymer.
[0131] The obtained block copolymer (B-1) had a triblock structure of (b2-1)-(b1)-(b2-2), and the composition ratio of (b2-1)-(b1)-(b2-2) was 12.5% by mass-75% by mass-12.5% by mass.
[0132] <Preparation of acrylic resins 2 to 5> Acrylic resins 2 to 5 were prepared in the same manner as for acrylic resin 1, except that the types and amounts of monomers were changed as shown in Table 1.
[0133] <Preparation of acrylic resin 7> 80 parts by mass of methyl methacrylate and 20 parts by mass of ethyl acrylate were added with 0.1 parts by mass of polymerization initiator (2,2'-azobis(2-methylpropionitrile)) and 0.24 parts by mass of chain transfer agent (n-octyl mercaptan) and dissolved to obtain a raw material liquid. Also, 100 parts by mass of ion-exchanged water, 0.03 parts by mass of sodium sulfate, and 0.45 parts by mass of a suspension dispersant were mixed to obtain a mixed liquid. A pressure-resistant polymerization vessel was charged with 420 parts by mass of the mixed liquid and 210 parts by mass of the raw material liquid, and the mixture was subjected to a polymerization reaction at a predetermined temperature while stirring under a nitrogen atmosphere, to obtain a polymer dispersion. The obtained polymer dispersion was washed with an appropriate amount of ion-exchanged water, and the polymer was taken out using a centrifuge and dried to obtain acrylic resin 7 (random copolymer).
[0134] <Acrylic resins 6 and 8-11> Acrylic resins 6 and 8 to 11 were prepared in the same manner as for acrylic resin 7, except that the types and amounts of monomers were changed as shown in Table 1.
[0135] The compositions and physical properties of acrylic resins 1 to 11 are shown in Table 1. [Table 1]
[0136] The weight average molecular weights (Mw) of the acrylic resins 1 to 11 and the polymer blocks, and the glass transition temperatures (Tg) of the acrylic resins 1 to 11 were measured by the following methods.
[0137] (Weight average molecular weight) The weight average molecular weight of the acrylic resin was calculated based on the molecular weight of standard polystyrene from a chromatogram measured by gel permeation chromatography in accordance with JIS K 0124-2011. The measurement device and conditions were as follows: Apparatus: Tosoh GPC device HLC-8220GPC Separation column: Shodex KF-G 4A + KF-805L x 2 + KF-800D Detector: RI detector Eluent:THF Eluent flow rate: 1.0mL / min Sample concentration: 0.1wt% / vol% Column temperature: 40℃
[0138] (Monomer mass ratio) next, 1 The abundance ratio of methacrylic acid esters (e.g., MMA) and acrylic acid esters (e.g., BA) in the acrylic resin was quantified by H-NMR using the integral ratio of the peaks derived from the methyl group and methylene group adjacent to the ester bond, and the monomer mass ratio was calculated.
[0139] (Mw of polymer block) The Mw of the acrylic resin measured by GPC was 1 The Mw of the polymer blocks (b1) and (b2) was calculated by multiplying by the monomer mass ratio determined by 1 H-NMR. The Mw of the polymer block (b2) was calculated as (total Mw-Mw of (b1)) / 2.
[0140] (glass transition temperature) The glass transition temperature of the acrylic resin was measured using DSC (Differential Scanning Calorimetry) in accordance with JIS K 7121-2012.
[0141] (pigment particles) Pigment particles: Titanium oxide (Teika Corporation "JR-805", average particle size: 0.29 μm)
[0142] 2-2. Preparation of fluororesin paint (Preparation of fluororesin paints 1-28) The fluororesin and acrylic resin were blended in the mass ratio shown in Table 2, and then the paint solvent component (isophorone) and the above-mentioned pigment particles were blended in an amount of 30 mass% relative to the total mass of the solids content. The resulting mixture was then filtered through a 500 mesh filter to remove aggregated particles from the mixture, thereby preparing fluororesin paints 1 to 28.
[0143] The resin compositions of the obtained fluororesin coating materials 1 to 28 are shown in Table 2.
[0144] [Table 2]
[0145] 3. Preparation and evaluation of painted metal sheets (Preparation of painted metal plates 1-28) The fluororesin paint shown in Table 3 was applied onto the undercoat layer of the coated original sheet prepared above, and then the plated steel sheet was heated so that the temperature reached was 250° C. Next, the plated steel sheet was immersed in water at 20° C. and cooled with water, and then removed from the water, the moisture was wiped off with gauze, and the plated steel sheet was dried indoors at 23° C. In this way, coated metal sheets 1 to 28 having a 20 μm-thick coating film (resin layer) of the fluororesin paint on the undercoat layer of the coated original sheet were prepared.
[0146] (evaluation) The initial workability, workability after storage, weather resistance, and coating hardness of the obtained coated metal sheets 1 to 28 were evaluated by the following methods. In addition, the coatings of the coated metal sheets 1 to 3, 21, and 23 to 27 were observed by TEM to observe the phase separation structure.
[0147] (processability) (1) Initial stage (immediately after painting) Within 2 hours after production, the resulting coated metal sheet was sandwiched between one or more test sheets of the same thickness with the coating facing outward, and folded 180° at 23°C. The minimum number of sandwiched sheets T at which no cracks appeared in the coating was recorded. The smaller the number of sandwiched sheets T, the better the workability.
[0148] (2) After storage The resulting coated metal plate was allowed to stand in an environment of 60° C. for 7 days, and then a 180° bending test was carried out in the same manner as above, and the minimum number of plates that could be sandwiched together without causing cracks in the coating film, T, was recorded.
[0149] (weather resistance) 1) First, the 60 degree specular gloss of the obtained coated metal sheets was measured using a gloss meter. 2) Next, using a Sunshine Weather Meter (manufactured by Suga Test Instruments Co., Ltd.) specified in JIS B 7753 Sunshine Carbon Arc Lamp Weather Resistance Tester, the coating surface was subjected to a 4,000-hour irradiation test with a black panel temperature of 63°C, a 60-minute cycle of 48 minutes of ultraviolet irradiation, 12 minutes of ultraviolet irradiation, and spraying. 3) After the test, the 60 degree specular gloss of the coating film was measured in the same manner as above, and the gloss retention (%) relative to the initial gloss was calculated. A higher gloss retention indicates higher weather resistance.
[0150] (Coating Hardness) The scratch hardness (pencil method) of the coating was measured in accordance with JIS K 5600-5-4 for the coated metal sheets within 2 hours after production (immediately after production) and for the coated metal sheets that had been left to stand at 60°C for 7 days (after storage).
[0151] (Transmission electron microscope (TEM) observation) The phase-separated structure was observed by a transmission electron microscope (TEM). 1) First, after embedding the resin layer, the surface was polished using an ultramicrotome and then steam staining with metal oxide was performed to selectively stain only the dispersed phase out of the dispersed phase and matrix phase. Next, ultrathin sections were prepared using an ultramicrotome to obtain TEM observation samples. These were then observed at 100,000 magnifications using a transmission electron microscope (TEM). 2) The particle sizes of 50 randomly selected stained domains (dispersed phase) from the obtained TEM images were measured, and the average of these was taken as the average particle size.
[0152] The evaluation results of the coated metal sheets 1 to 28 are shown in Table 3. Furthermore, the TEM observation results of the coated metal sheets 1 to 3, 21, and 23 to 27 are shown in Table 4.
[0153] [Table 3]
[0154] [Table 4]
[0155] As shown in Table 3, coated metal sheets 1 to 20, which contain a specific block copolymer as the acrylic resin, all have good processability and good weather resistance. Also, as shown in Table 4, the average particle size of the domains was 50 nm for coated metal sheet 1, 40 nm for coated metal sheet 2, and 15 nm for coated metal sheet 3, all of which were small.
[0156] In contrast, among the coated metal sheets 21-26 that do not contain a specific block copolymer as the acrylic resin but contain a random copolymer, the coated metal sheets 21-23 have low processability because the Tg of the acrylic resin is high and hard. On the other hand, the coated metal sheets 24 and 25 have good processability because the acrylic resin has a low Tg and is soft, but the weather resistance is low because the acrylic resin is generally deteriorated by ultraviolet rays and unevenness is formed between the acrylic resin and the fluororesin that is less likely to deteriorate by ultraviolet rays. The coated metal sheet 26 is a comparative example of the coated metal sheet 3, and is a random copolymer containing monomers of MMA and BA in the acrylic resin and having the same monomer mass ratio. Since the Tg of the acrylic resin is low, the processability is good, but since the acrylic resin phase-separates with the fluororesin to form large domains with an average particle size of 5 μm, the domains are decomposed and lost by ultraviolet rays, forming large unevenness on the surface, and the weather resistance is low. In this way, it is understood that it is difficult to achieve both processability and weather resistance when a random copolymer is used.
[0157] It is also found that even coated metal sheets 27 and 28 containing a predetermined block copolymer have low weather resistance. It was also confirmed that the average particle size of the domains of coated metal sheet 27 was 80 nm, which was larger than those of coated metal sheets 1 to 3. From these facts, it is considered that if the weight-average molecular weight of polymer block (b1) is too large, the domain size becomes large, which makes it easy for large irregularities to form on the surface after storage, thereby reducing weather resistance. [Industrial Applicability]
[0158] The coated metal sheet of the present invention has high workability and high weather resistance even after long-term storage. Therefore, it is expected that fluororesin-based coated metal sheets will become more widespread, particularly as exterior building materials.
Claims
1. A coated metal plate having a metal plate and a resin layer disposed thereon, The resin layer contains a fluororesin (A) and an acrylic resin (B), The acrylic resin (B) is a block copolymer including a polymer block (b1) of an acrylic acid ester having an alkyl group having 3 or more carbon atoms and a polymer block (b2) of a methacrylic acid ester, The weight average molecular weight of the polymer block (b1) is 40,000 or less. Painted metal plate.
2. The weight average molecular weight of the polymer block (b1) is 30,000 to 40,000. The coated metal sheet according to claim 1.
3. The weight average molecular weight of the polymer block (b2) is 2,000 to 20,000. The coated metal sheet according to claim 1 or 2.
4. the content of the polymer block (b1) in the block copolymer is 50 to 85% by mass based on the total content of the polymer block (b1) and the polymer block (b2); The coated metal sheet according to any one of claims 1 to 3.
5. The methacrylic acid ester is methyl methacrylate. The coated metal sheet according to any one of claims 1 to 4.
6. The acrylic ester having an alkyl group having 3 or more carbon atoms is n-butyl acrylate. The coated metal sheet according to any one of claims 1 to 5.
7. The block copolymer has the polymer block (b2) at both ends. The coated metal sheet according to any one of claims 1 to 6.
8. The glass transition temperature (Tg) of the acrylic resin (B) is −40 to −20° C. The coated metal sheet according to any one of claims 1 to 7.
9. The content of the acrylic resin (B) is 2 to 30% by mass based on the entire base resin of the resin layer including the fluororesin (A) and the acrylic resin (B). The coated metal sheet according to any one of claims 1 to 8.
10. The resin layer further contains an acrylic resin (C) having a glass transition temperature higher than that of the acrylic resin (B). The coated metal sheet according to any one of claims 1 to 9.
11. The resin layer further contains pigment particles. The coated metal sheet according to any one of claims 1 to 10.
12. The metal plate, the chemical conversion coating layer, the undercoat layer, and the resin layer are laminated in this order. The coated metal sheet according to any one of claims 1 to 11.
Citation Information
Patent Citations
Scratch-proof top coating composition
JP1991024145A
Highly durable coated metal plate with corrosion resistance in flaw part, processability, and snow slipperiness, and continuous manufacture of the metal plate
JP1995308633A
Coating composition
JP1997087575A
High hardness transparent fluoroplastic coated stainless steel panel and production method thereof
JP2001009367A
Fluororesin coated steel plate
JP2008087242A